Evaluation of Corrosive Substance Ingestion in the Pediatric Emergency Department - Raziye Merve Yaradılmış; Aytaç Göktuğ; Ali Güngör; İlknur Bodur; M. Mustafa Güneylioğlu; Betül Öztürk; Özlem Balcı; Derya Erdoğan; Can Demir Karacan; Nilden Tuygun (Galenos Yayinevi, 2023)
Introduction:The management of the patient who applied to the emergency department with corrosive substance exposure varies according to the characteristics of the substance and the clinical conditions of the patient. In this study; demographic and clinical characteristics, patient management strategies and prognosis of the children presenting with corrosive substance ingestion are presented.Methods:Cases who applied with corrosive substance intake and were under the age of 18 were included in the study. Demographic data of the patients, characteristics of the substance, presence of intraoral lesions or any symptoms or signs, treatment and prognosis, radiographs and hospital stay were examined. Drool scores were calculated.Results:One hundred-ten patients were included. The mean age of the patients was 41±13 months and 56 (50.9%) were male. 53% of the patients were asymptomatic at presentation. The most common symptom was nausea-vomiting, the most common finding was hyperemia in the oropharynx. The mean Drool score of the patients was 8.9±1.7. Seventy-seven patients (70%) took alkaline, 33 patients (30%) took acidic substances; 45 patients sodium hydroxide, 27 patients sodium hypochlorite, 26 patients took hydrochloric acid. Findings were mostly observed in hydrochloric acid and sodium hydroxide intake. Endoscopy was performed in 3 of the patients. The mean Drool score of the patients who underwent endoscopy was 6.7. No complications were observed in any of the patients in the follow-up.Conclusion:Ingestion of corrosive substances is one of the important and preventable causes of emergency department admissions with chemical poisoning. There is usually accidental and small amount of intake in early childhood. Patients may be asymptomatic or rarely present with severe symptoms. It is important to know the chemical content of the ingested substance in order to predict the risk of damage to the gastrointestinal tract and respiratory system and to provide appropriate management in emergency services.